Lifetime evaluation of left ventricular structure and function in male ApoE null mice after gamma and space-type radiation exposure - Brojakowska, Agnieszka; Jackson, Cedric J.; Bisserier, Malik; Khlgatian, Mary K.; Jagana, Vineeta; Eskandari, Abrisham; Grano, Cynthia; Blattnig, Steve R.; Zhang, Shihong; Fish, Kenneth M.; Chepurko, Vadim; Chepurko, Elena; et al. (Frontiers in Physiology, 2023)
The space radiation (IR) environment contains high charge and energy (HZE) nuclei emitted from galactic cosmic rays with the ability to overcome current shielding strategies, posing increased IR-induced cardiovascular disease risks for astronauts on prolonged space missions. Little is known about the effect of 5-ion simplified galactic cosmic ray simulation (simGCRsim) exposure on left ventricular (LV) function. Three-month-old, age-matched male Apolipoprotein E (ApoE) null mice were irradiated with 137Cs gamma (γ; 100, 200, and 400 cGy) and simGCRsim (50, 100, 150 cGy all at 500 MeV/nucleon (n)). LV function was assessed using transthoracic echocardiography at early/acute (14 and 28 days) and late/degenerative (365, 440, and 660 days) times post-irradiation. As early as 14 and 28-days post IR, LV systolic function was reduced in both IR groups across all doses. At 14 days post-IR, 150 cGy simGCRsim-IR mice had decreased diastolic wall strain (DWS), suggesting increased myocardial stiffness. This was also observed later in 100 cGy γ-IR mice at 28 days. At later stages, a significant decrease in LV systolic function was observed in the 400 cGy γ-IR mice. Otherwise, there was no difference in the LV systolic function or structure at the remaining time points across the IR groups. We evaluated the expression of genes involved in hemodynamic stress, cardiac remodeling, inflammation, and calcium handling in LVs harvested 28 days post-IR. At 28 days post-IR, there is increased expression of Bnp and Ncx in both IR groups at the lowest doses, suggesting impaired function contributes to hemodynamic stress and altered calcium handling. The expression of Gals3 and β-Mhc were increased in simGCRsim and γ-IR mice respectively, suggesting there may be IR-specific cardiac remodeling. IR groups were modeled to calculate the Relative Biological Effectiveness (RBE) and Radiation Effects Ratio (RER). No lower threshold was determined using the observed dose-response curves. These findings do not exclude the possibility of the existence of a lower IR threshold or the presence of IR-induced cardiovascular disease (CVD) when combined with additional space travel stressors, e.g., microgravity.